2023
DOI: 10.1002/ajhb.23983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on whole‐blood transcriptome profile in children with overweight/obesity

Signe Altmäe,
Abel Plaza‐Florido,
Francisco J. Esteban
et al.

Abstract: BackgroundThe current knowledge about the molecular mechanisms underlying the health benefits of exercise is still limited, especially in childhood. We set out to investigate the effects of a 20‐week exercise intervention on whole‐blood transcriptome profile (RNA‐seq) in children with overweight/obesity.MethodsTwenty‐four children (10.21 ± 1.33 years, 46% girls) with overweight/obesity, were randomized to either a 20‐week exercise program (intervention group; n = 10), or to a no‐exercise control group (n = 14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Furthermore, a recent systematic review reported that cardiopulmonary exercise testing is safe in children and adults with SCA 17 . Using a whole‐blood transcriptome profile (RNAseq) characterization approach could provide valuable insight into how the immune response reacts to acute exercise in paediatric patients with SCA 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent systematic review reported that cardiopulmonary exercise testing is safe in children and adults with SCA 17 . Using a whole‐blood transcriptome profile (RNAseq) characterization approach could provide valuable insight into how the immune response reacts to acute exercise in paediatric patients with SCA 18–20 …”
Section: Introductionmentioning
confidence: 99%